The effect of the MC4R gene on boar taint compounds, sexual maturity and behaviour in growing-finishing boars and gilts. (9th July 2015) - Van den Broeke, A.; Aluwé, M.; Janssens, S.; Wauters, J.; Vanhaecke, L.; Buys, N.; Millet, S.; Tuyttens, F. A. M.
Abstract : Societal pressure to ban surgical castration of male piglets is rising due to animal welfare concerns, thus other methods to prevent boar taint need to be explored. Genetic selection against boar taint appears to be a long-term sustainable alternative. However, as boar taint is linked to reproductive hormones, it is important to consider possible negative side effects such as delayed sexual maturity or changes in behaviour. We reported earlier that the melanocortin-4 receptor ( MC4R ) marker can be used to reduce boar taint levels in fat of boars. The objective of this study was to evaluate whether MC4R marker-assisted selection for lower boar taint prevalence affects plasma levels of boar taint compounds and testosterone; sexual maturity; behaviour; skin lesions; and lameness in boars and gilts. Using an intervention study with a 2×2 design, 264 boars and gilts differing on position 893 of the MC4R gene (AA v . GG) were compared. The MC4R polymorphism did not affect the plasma concentration of either androstenone or testosterone at different time points, whereas the concentration of skatole was significantly lower ( P= 0.003) and the concentration of indole tended to be lower ( P= 0.074) in GG compared with AA boars. A higher percentage of gilts of the GG genotype were in puberty at slaughter age compared with AA gilts ( P <0.001). The age of the boars at sexual maturity (as indicated by the first positive preputial smear test) did not differ between AA and GG boars. In contrast, weight of GG boars at sexual maturity tended to be lower ( P= 0.065). During the period from 6 weeks of age to slaughter, boars and gilts of the GG genotype showed more playing behaviour ( P= 0.015) and less passive and feeding behaviour ( P= 0.003). They showed more skin lesions on their back and caudal area ( P= 0.022), and tended to show more skin lesions on their head and anterior area ( P= 0.093) compared with AA animals. In conclusion, the polymorphism in the MC4R gene can be used as a marker without negative effects on reproduction characteristics in boars and gilts. Genetic selection towards a lower prevalence of boar taint will lead to more active pigs with more skin lesions. Management strategies may therefore be necessary to reduce skin lesions in the selected animals.